2018
DOI: 10.1007/s11356-018-2496-y
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons, phthalates, parabens and other environmental contaminants in dust and suspended particulates of Algiers, Algeria

Abstract: Chemicals such as polycyclic aromatic hydrocarbons (PAHs), phthalateesters, parabens, siloxanes and squalene, all of them classified as endocrine-disrupting chemicals (EDCs), have been reported to occur in all environmental compartments. The effects of EDCs on development, reproduction, growth, metabolism and obesity constitute a real public health issue. A list of EDCs (> 40 compounds) were characterised in total suspended particulates (outdoor soot: 92 samples) collected in July-September 2016 in an Algiers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…Contrary to what has been observed for alkanes, the PAH concentrations determined during the winter months are more important than those during the fall ones. This seems to match the general evolution of the meteorology dominating the Bou Ismaïl region, although the combustion processes are the main sources of these compounds (Khedidji et al, 2017;Rabhi et al, 2018). Indeed, the inversion of temperature Fig.…”
Section: Semi-volatile Organic Compounds (Svocs)supporting
confidence: 53%
See 1 more Smart Citation
“…Contrary to what has been observed for alkanes, the PAH concentrations determined during the winter months are more important than those during the fall ones. This seems to match the general evolution of the meteorology dominating the Bou Ismaïl region, although the combustion processes are the main sources of these compounds (Khedidji et al, 2017;Rabhi et al, 2018). Indeed, the inversion of temperature Fig.…”
Section: Semi-volatile Organic Compounds (Svocs)supporting
confidence: 53%
“…In the gas-phase, PAHs generally exist for a few hours or less and they might also react chemically and photochemically in the particle phase (Oliveira et al, 2014). One compound that is distinguished among the 16 PAHs classified by U.S. EPA is benzo(a)pyrene which is considered because of its strong carcinogenicity (Srogi, 2007;Rabhi et al, 2018), equivalent toxicity (dozens of ng m -3 ), and individual carcinogenicity index (several 10 -5 ) (Li et al, 2012). Triterpenoid hydrocarbons, better known as hopanes, are compounds mainly derived from bacteria such as bacterioparanols and produced during a geological period through diagenesis in sediments (Oros and Simoneit, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The sampling procedures and the analytical methods adopted by our team to characterize the composition of emissions and airborne particulates are described elsewhere [Ciccioli et al 1989, Yassaa et al 2001, Mabilia et al 2004, Mininni et al 2004, Paolini et al 2015, Rabhi et al 2018. Sampling procedures were based on active aspiration from effluents or air, respectively, for emissions and aerosols, while dust was collected from free surfaces according to method foreseen for depositions [Cecinato et al 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever pollution rouses acute or chronic harmful effects on humans and/or injures the environment, the knowledge of nature, rate and land spread of emissions results crucial in the perspective of mitigating the impact of toxicants [Albaiges et al 1984, Bascom et al 1996, Yassaa at al 2001, Ma et al 2015, Błaszczyk et al 2017, Sifakis et al 2017, Cetin et al 2018, Nieder et al 2018, Vaz 2018]. Hence, chemical and physical characterization of gas and particulate phases plays a primary role not only to picture the outcome of release of pollutants (i.e., evaluating concentrations of selected chemicals instantaneously or averaged over suitable times and comparing them with legislative requirements), but also to assess the relative importance of sources affecting the target site or land [Gundel et al 1993, Hecht 1999Ventrice et al 2013, Jedynska et al 2014, Giulivo et al 2016, Liu et al 2017, Praveena et al 2018, Rabhi et al 2018, Yuri et al 2018, Brehmer et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, the limited available studies involving short-term observations of outdoor PM-bound PAHs showed that the average concentrations in Algiers (Algeria) (7.47 ± 1.21 ng/m 3 ) [ 122 ] and Pretoria (South Africa) (4.11 ng/m 3 ) [ 123 ] were much lower than that in Kigali (Rwanda) (52.7 ng/m 3 ) [ 124 ]. On the other hand, Ofori et al [ 125 ] summarized the studies on the PAHs from 2005 to 2019 in Africa.…”
Section: Concentrations Of Atmospheric Pm-bound Pahsmentioning
confidence: 99%